The Erythroxylaceae of southern Africa : a metabolomical, genetic and chemotaxonomical evaluation - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2024)
Thesis (PhD (Medicinal Plant Sciences))--University of Pretoria, 2024.